Comparison of 3D printed and conventional denture base materials in terms of durability and performance characteristics - Zeynep Öztürk; Büşra Tosun (Scientific Reports)
Abstract The aim of this study was to compare the performance of denture base materials produced by three-dimensional (3D) printing and conventional methods in terms of their mechanical durability and water absorption and solubility properties. Conventional polymethyl methacrylate (PMMA) samples (Meliodent, Heraeus Kulzer, Germany) were prepared using the pressing technique. PowerResins (3BFAB Technology, Inc., Istanbul, Turkey) was used to produce the 3D printed denture base samples. The 3D printed samples were designed using Meshmixer software (Autodesk, Inc.) and printed on a DentaFab Sega 3D Printer (DentaFab, Istanbul, Turkey). Flexural and compressive strength and microhardness tests were conducted to evaluate the mechanical properties of the samples. Water absorption and solubility tests were also performed. The flexural and compressive strength and microhardness values ​​of the 3D printed group were higher than those of the conventional group (p < 0.001). The mean water absorption value was lower in the 3D printed group compared to the conventional group, and the difference between these values ​​was statistically significant (p < 0.001). A statistically significant difference was noted between the groups in terms of water solubility ​​(p = 0.003). Our study shows that 3D printing can produce customized and high-precision prosthetic bases while also improving their physical and mechanical properties.